Duodenal Chromogranin A Cell Density as a Biomarker for the Diagnosis of Irritable Bowel Syndrome - Magdy El-Salhy; Odd Helge Gilja; Doris Gundersen; Jan Gunnar Hatlebakk; Trygve Hausken (Gastroenterology Research and Practice)
Background and Aim. Chromogranin A (CgA) is a common marker for endocrine cells. The density of duodenal CgA cells is reduced in patients with irritable bowel syndrome (IBS). Methods. The present study was undertaken to evaluate the density of duodenal CgA as a biomarker for the diagnosis of IBS. Two hundred and three patients with IBS were recruited (180 females and 23 males; mean age, 36 years; range, 18–66 years). The control group comprised 86 healthy subjects without gastrointestinal complaints (77 females and 9 males; mean age, 38 years; range, 18–67 years). Biopsy samples were taken from the duodenum during gastroscopy. Sections from these biopsy samples were immunostained for CgA using the avidin-biotin complex (ABC) method. CgA cell density was quantified by computerized image analysis. Results. The CgA cell density was lower in IBS-total and in all of the IBS subgroups than in the controls. The sensitivity and specificity for a cutoff of <200 cells/mm2 were 86% and 95%, respectively. Conclusion. The duodenal CgA cell density seems to be a good biomarker for the diagnosis of IBS. It is an inexpensive, simple, and easy-to-use method that does not require sophisticated equipment or considerable experience.